Influence of particle size on flour and baking properties of yellow pea, navy bean, and red lentil flours. Issue 4 (16th May 2019) - Bourré, Lindsay; Frohlich, Peter; Young, Gina; Borsuk, Yulia; Sopiwnyk, Elaine; Sarkar, Ashok; Nickerson, Michael T.; Ai, Yongfeng; Dyck, Adam; Malcolmson, Linda
Abstract: Background and objectives: Pulse flours are produced by dry grinding pulses. Currently, no standards exist for the particle size of pulse flours. The objective of this study was to investigate how particle size affected the flour and bread‐baking properties of commercially milled pulse flours and those produced using a Ferkar mill. Findings: Finer pulse flours tended to have greater starch damage, lower water absorption capacity (WAC), and higher peak and final viscosities. Navy bean flour had a larger particle size distribution, lower starch damage, greater WAC, and lower peak and final viscosities due to presence of hull. Red lentil flour had a larger particle size distribution and higher starch damage than yellow pea flour. Bread made with finer pulse flours had better bread scores and a tighter, less open crumb structure. Bread volume was not affected by flour particle size, nor were the sensory properties of the bread in most cases. Conclusions: Particle size affected flour and bread‐baking properties of pulse flours indicating that particle size should be considered when formulating pulse‐based breads. Flours milled from whole pulses will have larger particle size distributions due to the presence of hull. Seed hardness will affect the grinding properties of pulses which will affect particle size and starch damage. Significance and novelty: Standardization of particle size for pulse flours would allow for consistency when sourcing flours from different suppliers. However, given that different particle size distributions may be better suited to certain applications than others, it may be more useful if suppliers specify the particle size similar to what is done with oat ingredients.